SARKASME DAN KETIDAKSANTUNAN BERBAHASA PADA AKRONIM PPKM DI MASA PANDEMI COVID-19 - Cahya Buana; Nailil Huda (Universitas Muhammadiyah Surakarta, 2023)
PPKM (Enforcement of Restrictions on Community Activities) is one of the government's policies in the context of tackling the Covid-19 pandemic in 2021-2022. This policy was responded to in various ways by the community, both in positive and negative ways. The negative responses include the use of sarcastic words for the PPKM acronym, different from its original meaning. Sarcasm in pragmatic studies is considered a form of language impoliteness because it makes other people humiliated. This study aims to: (1) find out the most popular PPKM acronym in the Covid-19 era, (2) analyze the type, purpose, and context of sarcasm in the PPKM acronym in the Covid-19 era, (3) reveal the manifestations of impoliteness in the acronym PPKM in the Covid-19 era. This study is qualitative research with a pragmatic approach as a basis for analysis, especially the language impoliteness theory used to analyze netizen comments on 7 YouTube channels. Based on the results of the study, it was found: (1) The most popular PPKM acronym in the Covid-19 era, such as